2022
DOI: 10.3389/fendo.2022.1035114
|View full text |Cite
|
Sign up to set email alerts
|

The dose-response relationship between sex hormones and hyperuricemia in different gender: NHANES 2013-2016

Abstract: ObjectivesTo access the dose-response relationship between sex hormones and hyperuricemia (HUA), and to find the cut-off value in different gender.Methods9,685 participants were derived from the database of National Health and Nutrition Examination Survey (NHANES). Restricted cubic spline (RCS) analysis were applied to explore the relationship between sex hormones and HUA after adjusting for confounding factors by propensity score match (PSM). Logistic regression was used to estimate the odds ratio (OR) and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In line with previous studies [12,15,17,21], our study demonstrated signi cant sex differences in SUA level and HUA prevalence. It may be explained by the differences in physiological hormone secretion, lifestyle such as smoking history and alcohol use, and diet habit between men and women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies [12,15,17,21], our study demonstrated signi cant sex differences in SUA level and HUA prevalence. It may be explained by the differences in physiological hormone secretion, lifestyle such as smoking history and alcohol use, and diet habit between men and women.…”
Section: Discussionsupporting
confidence: 92%
“…It may be explained by the differences in physiological hormone secretion, lifestyle such as smoking history and alcohol use, and diet habit between men and women. A logistic regression analysis showed that sex hormones had a dose-response relationship with HUA prevalence, such as estradiol and testosterone [21]. Furthermore, we found a U-shaped distribution of HUA prevalence along with the increase of age in female individuals, with highest HUA prevalence in the age group of over 50 years old.…”
Section: Discussionmentioning
confidence: 52%
“…44 By offering detailed insights on dietary habits, environmental exposures, drug trends, and adherence, NHANES fortifies the monitoring of nutritional health, food environs, and diet-associated behaviors and maladies. 45,46 Adherence to ethical considerations is paramount: all NHANES participants proffer written informed consent, facilitated by the approval of the Research Ethics Review Board of the National Center for Health Statistics. Furthermore, before any data dissemination, the National Center for Health Statistics undertakes stringent deidentification measures to uphold participant privacy.…”
Section: 21mentioning
confidence: 99%
“…Such findings offer fresh perspectives on diabetes pathogenesis in hyperuricemia patients. Intriguingly, Li 46 embarked on a detailed exploration of the NHANES database, aiming to decipher the dose‐response relationship between sex hormones and hyperuricemia and pinpoint threshold values across genders. Their exhaustive research unveiled a marked association: estradiol thresholds stood at 29.6 pg/mL for males and 23.6 pg/mL for females.…”
Section: Leveraging Public Databases For Enhanced Medication Adherenc...mentioning
confidence: 99%
See 1 more Smart Citation